Letters from a Father to His Daughter - Jawaharlal Nehru (Puffin Books, 2004)
It was the summer of 1928 when Jawaharlal Nehru was in Allahabad while his daughter was at Mussoorie and he wrote her many letters on various topics.Nehru conscientiously put his pen and its ink to use in this exercise over the length of that summer because he wanted his daughter to grow awareness about her circumstances and her environment and to his effect his letters were lucid and contained laconic precision. The complex topics of evolution, the genetic makeup and the difference in ethnicities and communities were all laid out to Indira in an initial slew of letters.He wished upon Indira an empathetic perception of the world and its conflicts and to that end he expounded the economics of deprivation, the peasant's woes and the division of labour. In another letter he wrote to Indira about the web of religion and how it manifested down to the people across time and its very origins. Here the rule of monarchy and the role played by kings and queens were discussed in detailed precision.His attempt was to infuse the young mind with a worldview that indulged both the history and the current environs of language and civilizations among other phenomenon. The economics of the eras weren't ignored and Nehru did his best in explicating the role of trade and the emergence of travel. He speaks about various topics like the Aryans and the arrival in India, Kings and Kingdoms of the past, and epics like the Mahabharata and Ramayana, in a manner which would appeal to a 10 year old.The letters that made up for lost time between father and daughter finally found their way into publication and is now a perfect guide for children into arousing their curiosity for their country and its people's history. Containing an introduction by Indira Gandhi, these letters that initially came into inception for the cause of educating his young daughter while he was away from home now serves as a treasure chest of knowledge for daughters and sons everywhere. Letters From A Father To His Daughter was first published in 1929.